Male And Female Profanity In Political Discourse - Marabyan, Luiza (Լիմուշ հրատ.)
The use of obscene language is not allowed in social life and in common human relations, moreover, it is not encouraged, acceptable or desirable. However, it is applicable in some levels of society and characterizes the behavior of a certain group of people. Considering that the social prohibitions reinforced by tradition ensure the mores of people inherited from the past, the traditions of life, they play an essential role in staying close to the original state of the past. Women are usually more committed to tradition than men. This circumstance is clearly observed not only in the attitude of men and women towards swearing, but also in the more differentiated attitude that society shows to women when they use swearing or obscene words. In this case, unlike a man, such an act of a woman is considered much more negative and unbearable. Հասարակական կյանքում, մարդկանց սովորական հարաբերություններում հայհոյանքի կիրառությունն արգելված է, իսկ եթե ավելի մեղմ՝ խրախուսելի, ընդունելի կամ ցանկալի չէ: Համենայնդեպս հասարակական ինչ-ինչ շերտերում այն կիրառելի է եւ բնութագրական՝ որոշակի խմբի մարդկանց վարքագծին: Հաշվի առնելով այն, որ ավանդույթի ուժ առած հասարակական արգելքներն ապահովում են մարդկանց՝ անցյալից ժառանգած բարքերը, կենցաղի ավանդականությունը, ուրեմն՝ դրանք էական դեր են խաղում անցյալի նախնական վիճակին հարազատ մնալուն: В общественной жизни, в обычных человеческих отношениях использование нецензурной лексики запрещено, а если помягче выразиться, то не поощряется, не приемлемо и не желательно. По крайней мере, в некоторых слоях общества оно применимо к поведению определенной группы людей. Учитывая, что укоренившиеся в традициях социальные барьеры обеспечивают людям унаследованные от прошлого нравы и традиции жизни, они играют существенную роль в сохранении близко к исходному состоянию прошлого. Обычно женщины более привержены к традициям, чем мужчины. Это отчетливо видно не только в отношении к нецензурной лексике мужчин и женщин, но и в более дифференцированном отношении, которое общество проявляет к женщинам, когда они используют нецензурную брань или нецензурную лексику.
Keywords: Linguistics